Esthétisation du chronotope dans Les Empreintes d’une saison de Joseph César AFUNDI Monene. - Mutombo, Alexis KATAMBWA (IJRDO - Journal of Social Science and Humanities Research, 2022)
Our study deals with the aesthetization of chronotope in “Les Empreintes d’une saison” de Joseph César AFUNDI Monene. Under the light of literary semiotics, we have pointed out in the work under study 3 relevant examples of chronotope: problematic time-space, apocalyptic time-space and nostalgic time-space. The problematic time-space explores a double dimension, national and planetary, putting accent on the dramatic events which brought death in Kisangani during the six days’ war on the one hand and the destruction of the earth planet, our common nation, on the other hand. The apocalyptic time-space is built of premonitory dreams for a best tomorrow. At last the nostalgic time-space is full of remembrances having a joyful frame of rustic area presented symbolically as a safety and suitable place against the atrocities of the present moment and the fearful uncertainties of tomorrow.